Implementación de una granja escolar que permita desarrollar la sensopercepción en los estudiantes de la escuela Francisco Daquilema de la provincia de Cotopaxi, en la parroquia Zumbahua, comunidad Ponce en el año 2012-2013. - Chiguano Pastuña, Juan Geovanny (2012)
The implementation of a farm or green house in a school will facilitate the development of several methods, abilities and strategies in the students about thesensoperception. It is very important to develop in the children activities related with what corresponds to the cultivation of little agricultural farms or school greenhouses where they will have the possibilities of growing legumes, vegetables, fruit and cereals in a planned way with a guide by the teacher who will focus on giving information about the benefits that grown products give in an organic manner, free from the utilization of chemicals that affect health. One of the goals is that children can be able to share this information with their parents in their homes. This work also attempts to be a support to protect and taking care of the environment.